ISOLATION PINOSTROBIN COMPOUND IN TEMU KUNCI (KAEMPFERIA PANDURATA ROXB) RHIZOME - Nurul Indriani; Muhammad Eka Putra Ramandha (Program Studi Kimia, Universitas Lambung Mangkurat, 2023)
Isolation and identification of Pinostrobin compounds in Temu Kunci Rhizomes (Kaempferia pandurata Roxb) were conducted in this study. The isolation and identification methods used were extraction, crystallization & recrystallization, Thin Layer Chromatography, and (4) Infrared (IR) Testing. The extraction results were followed by crystallization and recrystallization processes. The recrystallization produced a yellow solid isolate. A Thin Layer Chromatography test was carried out to determine the purity of the isolate using the eluent Chloroform : n-hexane of 6:4, Chloroform : Ethylacetate of 7:3. A comparison of the Retention Factor (Rf), and the Rf value of the phinostrobin standard indicates that the positive test sample contained the Pinostrobin compound. The Infrared spectrum indicates that the sample belongs to the flavonol group. It is confirmed from the functional groups of the isolates that are compatible or identical to the functional groups in the pinostrobin compound.